The Symbolic Meaning Of Motif Lereng Batik Garutan - et. al., M. Firdaus Benyamin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Batik Garutan (Garut batik textiles) is part of Garut’s cultural heritage with historical and aesthetic values. The decorations of batik Garutan are naturalistic and reflect the characteristics of batik produced in coastal areas, because they receive cultural influences from other batik-producing areas such as Cirebon, Yogyakarta, Solo, Indramayu, Pekalongan, and even China. The creating mechanism of batik Garutan emphasizes more on the traditional values and habitual patterns that have been passed down through generations by adopting requests and orders from certain customers, but also based on the tastes of the batik craftsmen. In particular, batik Garutan contains no specific symbolic meaning, but the theme is being adapted to the form of the decoration. The characteristic of batik Garutan’s color composition is by using beige or gumading color. The visualization of batik Garutan is illustrated by its decorations, such as basic geometric shapes, geometric with fauna, geometric with flora, floral-shaped diagonal lines, and basic geometric shapes with flora and fauna. The lereng (slope) is the most dominant motif of batik Garutan. In general, it is shaped as ornament placed sideway or diagonal, and the pattern is almost the same, which is a repetition of certain forms. This study was conducted using qualitative methodology by collecting a variety of secondary data in order to understand more about the phenomenon, as well as using inductive approach in analyzing it. The aim of this study is so people could be aware of the characteristics of lereng motif and know about the symbolic meaning contained in each lereng motif in batik Garutan. Batik Garutan should be able to highlight its trademark as efforts to introduce and improve the existence of batik Garutan to be better known by various groups, so that it could be promoted appropriately, both domestically and internationally.